Impacts of low dose gamma rays on hematological parameters in Wistar albino rats: In-vivo - Pirkhider Yaba, Sardar (Zanco Journal of Medical Sciences (ZJMS), 2026)
Background and objective: The effects of gamma radiation dosages on the hematological parameters of albino rats were examined through in-vivo exposure methodologies. Methods: Cesium-137 was utilized as a source of ionizing radiation, and various doses were administered via appropriate irradiation collimators. The subjects comprised 30 female albino rats, each with a mass of 200±10 grams, with the duration of exposure for each irradiation source calibrated individually. The principal hematological components (including white blood cells, red blood cells, and platelet counts) of the female rats were assessed employing direct exposure methodologies for low radiation doses. Results: The results indicated that variations in the optimum time of exposure were 15 minutes. High doses of ionizing radiation have a considerable effect on the primary blood components. The radio-sensitivity and physiological properties of each kind of blood component determined the optimal irradiation dosages that resulted in high WBC, RBC, and PLT densities. Radiation doses had a substantial impact on PLT density, reduced with 42% compare to the control value (P-value < 0.05). Conclusion: Ionizing radiation had a relatively small effect on the density of the main blood components after a limited amount of exposure. The type of blood components determined the optimal radiation doses with high efficiency on component density. Furthermore, high impacts (very significant) concentrated on PLT density.